Location and survival of MNEs' subsidiaries - Mariotti, Sergio; Mosconi, Rocco; Piscitello, Lucia (Strategic Management Journal, 2019)
[Research summary:Our study provides a quasi–replication of Shaver and Flyer (2000), which was among the first studies that challenged the positive role of agglomeration in determining companies' location choice and performances, thus changing the way management scholars view companies' attitude towards agglomeration forces. We employ the same research design, specification and tests, and a different population, to discuss the generalizability of the original study. Building on the framework of Shaver and Flyer (2000), our findings offer intriguing new empirical evidence highlighting the importance of the differential between entering foreign firms and host country firms as a crucial condition in understanding agglomeration forces and adverse selection mechanisms. Managerial summary:Our exercise confirms that agglomeration forces act differently on stronger versus weaker multinational enterprises (MNEs). However, we find that stronger MNEs tend to avoid location in highly specialized areas when they are afraid of knowledge leakages towards host country–based rivals that have enough absorptive capacity to benefit and improve their competitive advantages. Managerial implications are quite relevant. Indeed, when MNEs avoid co–location in highly specialized areas, they also limit their own access to local knowledge and other agglomeration economies, such as supply networks and qualified workforce. Thus, MNEs managers need to design and implement devices that, on the one hand prevent local leakages of their knowledge and, on the other, do not hinder their access to local unique knowledge and resources.]